Autophagy in dry eye disease: Therapeutic implications of autophagy modulators on the ocular surface - Nallathambi Jeyabalan; Aswathi M Pillai; Pooja Khamar; Rohit Shetty; Rajiv R Mohan; Arkasubhra Ghosh (Indian Journal of Ophthalmology, 2023)
Dry eye disease (DED) is a chronic ocular surface disorder, associated with inflammation, which can cause severe morbidity, visual compromise, and loss of quality of life, affecting up to 5–50% of the world population. In DED, ocular surface damage and tear film instability due to abnormal tear secretion lead to ocular surface pain, discomfort, and epithelial barrier disruption. Studies have shown the involvement of autophagy regulation in dry eye disease as a pathogenic mechanism along with the inflammatory response. Autophagy is a self-degradation pathway in mammalian cells that reduces the excessive inflammation driven by the secretion of inflammatory factors in tears. Specific autophagy modulators are already available for the management of DED currently. However, growing studies on autophagy regulation in DED might further encourage the development of autophagy modulating drugs that reduce the pathological response at the ocular surface. In this review, we summarize the role of autophagy in the pathogenesis of dry eye disease and explore its therapeutic application.